Effect of two palms (Borassus aethiopum and Hyphaene thebaica) on the physicochemical characteristics of the soil of the agroforestry parklands in Gaya (Niger) - Abdoulaye Garba-Seyni; Hama Oumarou; Vidal Barron; Hamissou Amadou Mounkaila; Antonio Navajas; Rafael Villar (European Scientific Journal, ESJ, 2025)
The management of soil fertility is a major issue worldwide. The aim of this study was to determine the contribution of B. aethiopum and H. thebaica to soil fertility in south-west Niger. Using a complete randomized design with three replicates. 45 composite samples of 100 g of soil (36 below canopy and 9 outside) were collected between 0 and 20 cm depth and used to determine organic matter content, total carbon, total nitrogen and total sulfur, macronutrients (Mg, Ca, Na and K), Olsen phosphorus, micronutrients (Fe, Zn, Cu and Mn), pH, hygroscopic moisture, electrical conductivity and texture. The results showed that organic matter, C, N, Mn, Mg, Zn, hygroscopic moisture, P and Fe were significantly higher under the crowns of both species but with a higher effect of B. aethiopum canopy. Variations in their levels, with the exception of P, were explained by soil organic matter, to which they were significantly well correlated. This study showed that B. aethiopum and H. thebaica significantly improve fertility and contribute to soil stability. In view of these results, it is essential to devise policies for the rational management of forest resources as an alternative to the sustainable conservation of stability and crop soil fertility.